Strategi Manajemen Belajar Santri Di Lembaga Pendidikan Al-Qur’an (LPQ) Al-Falah - Rizki Wahid Hidayat; M. Adin Setyawan (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2023)
Management strategy is a process or series of activities by making basic and comprehensive decisions, along with how to implement them and made by top management and implemented by all levels within an organization. The decline in children’s interest in learning is caused by several factors, namely internal factors from their education and external factors from outside their education. There needs to be a strategy and efforts that must be carried out by an institution by taking early prevention of the decline in interest in studying students after they are teenagers, so that later a child can continue to follow Al-Qur’an learning until he completes his education. The purpose of this study is to describe the efforts and strategies implemented by the education system at LPQ Al-Falah, and to describe the factors that influence the decline in students’ interest in learning after adolescence. This research method uses qualitative research with descriptive qualitative as a research approach. This research is based on primary and secondary data collected through observation, interviews, and documentation. Then the data analysis technique used is descriptive narrative analysis which describes a narrative of what is being studied regarding the whole or part of the experience of the individual or of the group studied. The results of this study are the efforts and strategies carried out by LPQ Al-falah to prevent the decline in students’ interest in learning, by applying differentiating learning materials, applying good methods, conditioning the learning environment, collaboration techniques, and increasing the spirituality of students. While the factor of decreased interest in learning is the emergence of factors from within the Institution and factors from outside the Al-Qur’an Al-Falah educational institution. Keywords: Management Strategy, Reducing Students’ Interest in Learning, Early Prevention.